Developing of Thesis Guidance Learning Media Using The Five Stage Model (MANTAP) in French Language Study Program - Zulherman Zulherman; Dedy Kiswanto; Rabiah Adawi (JETL (Journal of Education, Teaching and Learning), 2024)
The COVID-19 pandemic has been proven to have a significant impact on changes in various aspects of human life, including education. One group that is specifically affected is final semester students who face challenges in the thesis preparation process due to the large-scale social restriction (PSBB) policy in Indonesia. With limited social interaction and face- to-face learning, the thesis guidance process becomes more complex, increasing the psychological and academic burden for students. including the thesis supervision process for French Language Students at Medan State University. As an alternative solution, research was carried out by examining the use of GitHub as a cloud storage medium and Telegram as a communication platform to speed up the thesis guidance process, where when students make corrective changes to the thesis files contained in Github, the lecturer will automatically get the information via notification on Telegram. This research uses  the MANTAP model in system development, where the results of each stage will become input for the next stage so that the process of improving each other occurs. The test results of the real-time notification system show that the notification messages to lecturers and students are completely accurate, namely 100%, meaning that every change made to the thesis file on Github will be notified automatically by Telegram. Apart from that, from measuring the system response time with 2 scenarios, it was found that the average response time was very good based on QoS (Quality of Service) standards, namely 0.47 ms for scenario 1 and 0.82 ms for scenario 2, this difference is the average response time for scenario 1 and scenario 2 This occurs due to differences in internet speed for each collabator which has an impact on differences in response time obtained.